Chemical laboratory safety and management: a training module for secondary schools - Abd Hamid, Shafida; Wan Abdul Khodir, Wan Khartini (2021)
This is a module used in the training programme for the science teachers in technical staff in secondary schools to promote good lab management and practices for the school communities.